“MAKE THE GHOSTS REAL”: FEMALE MOURNING IN NAOMI WALLACE’S IN THE HEART OF AMERICA & A STATE OF INNOCENCE - Chun-Yi, Shih (2014)
This paper will attempt to explore the female mourning in Naomi Wallace’s In the Heart of America (1994) and A State of Innocence (2008). The first part will trace back to the traditional burial ritual and Greek tragedy and discuss the major themes of female mourning and its significance. The second part will consider In the Heart of America. In the play, the ghost of Lue Ming, a Vietnamese woman, appears in search of Lt. Calley, the leader of My Lai massacre. Lue Ming and her infant daughter were both killed in the massacre; her grief over her loss and search for Calley denounces America’s imperial brutality of killing hundreds of old men, women and children in Vietnam. The third part will deal with A State of Innocence, based on a real event in the Israeli-Palestinian conflict. Um Hisham, a Palestinian woman, mourns for two deaths: that of her beloved girl accidentally killed by an Israeli army and that of Yuval, an Israeli soldier who helped her and later died in her arms. Her mourning condemns the de-humanization of war, but it also goes beyond condemnation to highlight the connection between the opposite sides and the re-humanization of one side to the other. The last part will bring up Judith Butler’s Precarious Life (2004), in which she contends that conventions of mourning are normally shaped by the state; while particular lives are deemed valuable and mournable, certain deaths are disavowed as deaths. The women in Wallace’s two plays mourn for the innocent victims of war, for the deaths that are not mourned or grieved by the nation; the female mourning not only protests against war but also proposes peace and life.